Strategi Atribut Produk dalam Meningkatkan Hasil Penjualan Pawon Mbak RU DSN. Ngloji, Magelang - Sulistiyaningsih, Sri; Proborini, Ellen; Ismanto, Fiderius; Mulyanto, Kukuh; Hendriyanto, Asepta; Husain Asy’ari, Fajar; Effendi, Meizar (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Strategies for product attributes are crucial for increasing a company's attractiveness and competitive edge. According to observations, insufficient marketing and promotion elements continue to hinder the Pawon Mbak Ru company in Dusun Ngloji, Magelang, from optimizing sales performance. Therefore, in order to maximize product qualities and increase consumer appeal, a suitable technique is required to build a marketing strategy. The purpose of this study is to create and apply product attribute methods to enhance Pawon Mbak Ru's sales performance. As part of the marketing plan, promotional items including business banners, directional signs, logos, and stickers are created as part of a practical community service manner. The outcomes of this service demonstrate that Pawon Mbak Ru has a more efficient way to market their company to prospective clients and the local community by developing a variety of visual features. While logos and stickers provide the company image a sense of professionalism and distinctive appeal, business banners and directional signs assist make the business location more accessible. Overall, Pawon Mbak Ru's increased sales results in Dusun Ngloji, Magelang, have been supported by the application of this product attribute strategy, which has improved business attractiveness.